THE RELATIONSHIP AMONG LEARNING INDEPENDENCE, THE LOGICALLY THINKING ABILITY AND LEARNING ENVIRONMENT AT HOME WITH MATHEMATICS LEARNING OUTCOMES OF STUDENTS GRADE XI OF AUDIO VIDEO MECHANICAL DEPARMENT IN SMK NEGERI 1 PUNDONG BANTUL YOGYAKARTA - Novita Candrawati; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
The lack of seriousness and independence of student learning, logically thinking ability of students who have not undeveloped, and learning environment at home that is not condusive are factors which affect the results of learning mathematics. This research aims to determine whether there is a positive and significant relationship among learning independence, logically thinking ability and learning environment at home with mathematics learning outcomes of students grade XI of audio video mechanical (AVM) deparment in SMK Negeri 1 Pundong Bantul Yogyakarta in even semester in academic year of 2015/2016. The population in this research is a class XI AVM student of SMK Negeri 1 Pundong. Samples were taken using the techniques random sampling and obtained a class XI AVM as a sample. The data collection was conducted by questionnaire and tests. Testing instrument using validity test, different power test and reliability test. Data were analyzed using analysis prerequisite test including normality test and independently using Chi-square formula, linearity test using the formula F-test and hypothesis testing using t-test. The results showed a positive and significant correlation between: (1) learning independence with mathematics learning outcomes, with = 0,1534 and  = X1;(2) the ability to think logically with mathematics learning outcomes, with 0,3524 and  = X2; (4) learning and the ability to think logically with mathematics learning outcomes, with 0,4276 and  = ; (6) the ability to think logically and learning environment at home with mathematics learning outcomes, with  0,3628 and  = (; (7) learning independent, the ability to think logically and learning environment at home with mathematics learning outcomes, with 0,4276 and  = (.